The value of accurate clinical assessment in the surgical management of the lumbar disc protrusion. Issue 2 (February 1988) - Kerr, R S; Cadoux-Hudson, T A; Adams, C B
Abstract : One hundred patients with lumbar disc protrusions were studied. Thirty six "control" patients were admitted in the same time period with low back pain and sciatica but with subsequently "normal" myelograms and no surgery. The aim of this paper was to relate history and clinical signs to the myelograms and surgical findings. Ninety nine per cent of our patients presented with sciatica (controls 94%). The most frequently found sign in patients with a disc protrusion was reduction of ipsilateral straight leg raising (98%). However, 55% of controls also showed this sign. There were three signs that, when present, particularly indicated a disc protrusion; "crossed straight leg raising" (pain on contralateral straight leg raising), measured calf wasting and impaired ankle reflex: the latter being especially indicative of an L5-S1 disc protrusion. There were two further important signs, weakness of dorsiflexion of the foot and scoliosis of the lumbar spine. However, such signs occurred in about half the patients and so clinical diagnosis in the remaining half depended on obtaining a good history of sciatica, and paying due regard to severity of the pain, the mobility of the patient, the ability and desire to work and the overall personality. Satisfactory results of surgery simply depend on finding and removing a definite disc protrusion. Using these methods of selection, 98% have returned to their original employment, 86% within 3 months of the operation. For a patient with no abnormal signs and a normal myelogram, surgical treatment should not be advised.